Compet??ncias empreendedoras na gest??o de conflitos: um estudo explorat??rio em clubes esportivos sociais - Campos, Jo??o Gurgel de (2017)
Sport has been considered a very important product for the world economy and sports management plays a fundamental role in the development of sports and sports organizations in the world. Even with all this relevance, little is produced scientifically on the subject in Brazil. The choice for social sport clubs as a research environment is due to the fact that they are considered models of non-profit organizations whose essence is directed towards their associate. Because it is a type of organization that in its management has a hybrid model composed of voluntary statutory sports managers (president, directors and advisers), and remunerated sports managers (managers, supervisors, coordinators and leaders, among others) As management concomitantly concludes, if there are conflicts between these two levels and, to this end, it is necessary to know the actions and competencies of its leaders. Thus, this research aims to identify the competencies of managers of social sports clubs and whether these competencies are entrepreneurial. It is a qualitative research, exploratory in nature and the instrument of data collection is the interview, supported by a semi-structured script. The data were treated in the light of content analysis, according to Bardin (1977) guidelines. The results show that there is a diversity among the types of conflicts existing in social sports clubs, and through the study of Man and Lau (2005), the research mapped the entrepreneurial competences used by the managers involved. It was possible to observe applicability of the typology of entrepreneurial competences on the actions of managers in the management of conflicts. The conclusions warn of the need to develop an entrepreneurial look at the competencies of managers. The reports of sports managers also indicate that there is knowledge among them that they live in a conflicting environment, due to the organizational structure. Faced with conflict management, it was clear that there are differences between voluntary and paid managers, although both have entrepreneurial competences in their prevention and manipulation. In this way, the study contributed to the academic development of conflict management and entrepreneurial competences in relating the themes, as well as generating a still incipient material in Brazil about social sports clubs and their administrative model.